Measuring the economic empowerment of women using an index an application to small-scale fisheries and agriculture in Sebaste, Antique. - Dionela, Ritchie Ann A.; Tabuena, Jorilyn (2016.)
This study measured the economic empowerment of women from small-scale fisheries and agriculture sector of Sebaste, Antique. There were a total of 199 respondents selected using stratified random sampling. The Five Domains of Empowerment (5DE) Index was used in measuring the economic empowerment of study participants. Through this composite index, it was determined how women scored in the five domains of empowerment, namely production, resources, income, leadership, and time. The result of the study shows that women fishers are more economically empowered than women farmers. The two sectors showed high disparity in their scores on input in productive decision; autonomy in production; ownership of assets; control over use of income; group member; speaking in public; workload; and leisure. Group member indicator contributed largely to the disempowered population in both sectors. Although income of women farmers is higher than that of women fishers, the latter are still economically empowered which suggests that economic empowerment is not dependent on income alone. The study recommends that fisheries and agriculture organization for women should be established so that their needs and concerns will be heard and addressed. It is further recommended that government projects focused on enhancing women empowerment should also give importance on other factors such as organization and leisure and not just income to totally promote of women empowerment. Further studies on measuring women?s empowerment using other methods should be pursued to provide more information on women's well-being.
Research Paper (Undergraduate, Bachelor of Science in Economics) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Women -- Economic Empowerment; Small-scale fisheries; Sebaste, Antique